Scarcity and Consumption Priorities - Momi Dahan; Doron Sayag (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper focuses on whether households facing economic scarcity tend to change consumption priorities as measured by the share of spending on necessity goods relative to luxury goods in a large national supermarket chain in Israel for the years 2011–2018. Based on detailed weekly revenue data from that supermarket chain, we found that in weeks of economic scarcity (i.e., weeks without payments of social security allowances or salary), the spending on necessity goods, which are regulated products, is down by 4.8%, but the cut in spending on luxury goods is even more pronounced at 8%, and the difference between these two types of goods is up significantly by 3.2%. Within the luxury category, we observe a 10% or more decline in feast-related goods, indicating a "feast and famine" consumption strategy. Nevertheless, spending on food with label claims such as gluten-free and omega-3 eggs, is smaller (6%) than the overall spending on luxury goods in scarcity week but more than the overall spending on necessities.
Keywords: D12; I30; 330; scarcity; consumption; necessity; luxury